Prevalence of pregnancy varicose and its effective factors in women referred to gynecology hospitals in Tabriz - Dara Alvandfar; Mahrokh Alizadeh; Mehdi Khanbabayi Gol (Mashhad University of Medical Sciences, 2019)
Introduction: Regarding to the lack of reports about the prevalence of pregnancy varicose in Iran and the adverse effects of this type of varicose on pregnancy and childbirth, this study was performed with aim to evaluate the prevalence of pregnancy varicose and its related factors. Methods: This analytical-cross-sectional study was performed on 275 pregnant women in gynecology hospitals of Tabriz in 2018. The CEAP checklist was used to determine the severity of varicose symptoms. Data were collected by the researcher after completion. Data were analyzed by SPSS software (version 20) and spearman correlation test. P<0.05 was considered statistically significant. Results: The prevalence of pregnancy varicose was 18.18% (n=50), and among women who had varicose, the majority (n=26, 9.4%) had mild varicose. Also, there was significant relationship between pregnancy varicose and age (P=0.005), BMI (P=0.02), gestational age (P=0.001), smoking (P=0.01) and history of deep vein thrombosis (P=0.03). Conclusion: The prevalence of pregnancy varicose in the present study was about 18.2%. The factors such as age, body mass index, gestational age, smoking and history of deep vein thrombosis are among the main factors affecting the disease.